Effects of soil moisture on 13C assimilate redistribution and grain yield components in wheat - Zhang, Zhen; Yu, Zhenwen; Shi, Yu; Zhang, Yongli (Frontiers in Plant Science, 2025)
IntroductionIn order to solve the current situation of water shortage and achieve sustainable agricultural development, micro-sprinkler water-saving irrigation is one of the effective methods to improve water use efficiency (WUE) compared with flood irrigation. However, the effects of water content on wheat grain weight and plant hormone content under micro-sprinkler water-saving irrigation, and the potential mechanism of different water content on plant hormone-mediated grain grouting under micro-sprinkler water-saving irrigation are still largely unknown. MethodsTherefore, this study conducted extensive monitoring of wheat grain weight and plant hormone content under different water content in a typical winter wheat field (wheat) in the North China Plain from 2019 to 2021 by 13C isotope tracer technology through a field experiment based on micro-sprinkling water-saving irrigation.ResultsThe results showed that under micro-sprinkler water saving irrigation, the lateral development of wheat roots after anthesis was promoted by W3 treatment in the deep soil depth (0-60 cm), which was the basis for efficient absorption of water and fertilizer, as well as efficient formation of photosynthate. Meanwhile, W3 treatment significantly promoted the transfer of photosynthetic products from leaves, stems and sheaths to grain. Compared with other treatments, W3 treatment significantly increased the average grain filling rate and grain filling time. Compared with W1, W2 and W5 treatments, W3 and W4 treatments significantly improved the number of grains per ear, 1000 grain weight and grain yield. From the perspective of water saving, W3 treatment had the highest effect. Compared with W1, W2 and W5 treatments, W3 treatment significantly increased the average grain yield of the two seasons by 19.69%, 6.30% and 8.07%, respectively.DiscussionIn this study, optimizing micro-sprinkler water saving irrigation can improve root development, promote photosynthetic product transport, and increase average grain filling rate and grain filling time, thereby increasing grain yield.This study provides valuable insights into improving sustainable wheat production in micro-water-saving irrigation agricultural cropping systems, and it may provide a practical framework for striking a balance between groundwater protection and food security.